2004
DOI: 10.1111/j.1464-5491.2004.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Is human Type 2 diabetes maternally inherited? Insights from an animal model

Abstract: We therefore conclude that there is no evidence for maternal transmission of diabetes in the GK rat. Mothers were able to adjust their supply of milk so that offspring attained similar weights independent of litter size. The weight of the offspring remained independent of litter size into adult life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Our results confirm the importance of genetic factors in crosses are more hyperglycaemic than those of Wistar female/GK male crosses and this has also been taken as evidence of the diabetogenic effects of being exposed to diabetes in-utero [17]. However, these maternal effects have not been confirmed in other studies [18,19] and the experiments are hampered by the fact that the offspring also share the maternal (non-diabetogenic) genes. Our embryo-transfer model removes this potential confounding factor, since offspring have not inherited genetic material from their surrogate mothers.…”
Section: Discussionsupporting
confidence: 32%
“…Our results confirm the importance of genetic factors in crosses are more hyperglycaemic than those of Wistar female/GK male crosses and this has also been taken as evidence of the diabetogenic effects of being exposed to diabetes in-utero [17]. However, these maternal effects have not been confirmed in other studies [18,19] and the experiments are hampered by the fact that the offspring also share the maternal (non-diabetogenic) genes. Our embryo-transfer model removes this potential confounding factor, since offspring have not inherited genetic material from their surrogate mothers.…”
Section: Discussionsupporting
confidence: 32%
“…Animal studies demonstrate that metabolic imprinting caused by the diabetic intrauterine environment can be transmitted across generations (7)(8)(9). In humans, excess maternal transmission of type 2 diabetes (10,11) supports the hypothesis that the intrauterine environment, independent of genetic transmission, contributes to increased risk of type 2 diabetes in offspring.…”
mentioning
confidence: 61%
“…For example, in the Goto Kakizaki-Wistar rat model of type 2 diabetes, studies in reciprocal F 1 populations with identical nuclear genomes but different mitochondrial genomes failed to show any consistent effects on glucose metabolism that might be attributed to sequence variants in the mitochondrial genome (Gill-Randall et al 2004). In a study of reciprocal F 1 populations derived by crossing a glucose-intolerant strain of BHE/Cdb rats with Sprague-Dawley rats, Mathews et al (1999) reported that impaired glucose tolerance was associated with inheritance of a point mutation in the mitochondrial gene encoding ATP synthase subunit 6.…”
Section: Discussionmentioning
confidence: 99%